Expanding the Feminist Pathways Perspective beyond the United States: a Profile of Federal Women Prisoners in Argentina - Salisbury, Emily J. (Women & criminal justice, 2018)
A large body of knowledge within the criminological discipline has demonstrated that women and girls have distinct social and psychological risk factors that contribute to both their initial onset, and continued engagement, in offending behavior. However, most of this research has focused on U.S. samples of women offenders. Using mixed methods, the current research investigated the offense dynamics and possible risk factors for women’s imprisonment with incarcerated women (246 survey respondents; 12 interviewees) in the Argentine federal penitentiary system. We find that there are some similarities in the characteristics of women prisoners in Argentina and the characteristics of women prisoners in the United States, but also some distinctions, primarily in the prevalence of prior victimization. In addition, our results indicate that federal women prisoners in Argentina who reported serious prior abuse were more likely to have committed crimes against persons in comparison to women without abuse histories. Such a distinction supports the ongoing research investigating women offender profiles beyond U.S. samples.